The Effect of Using Video on Students’ Listening Comprehension Skill - Dzikri, Afdhal; Eliwarti, Eliwarti; Supriusman, Supriusman (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aimed at examined if there is a significant effect of using video on SMAN 1 Inuman students' listening comprehension skill. This research used quantitative research was used pre-experimental design. One-Group Pretest-Posttest as a research design. In this design, one group was selected to measure level of progress before and after treatment. Researcher was applied a normality test to ensure the data was normally distributed and continued with the paired sample T-test. Based on the data analysis, there was a fairly large difference between students learning outcomes before and after using videos in listening comprehension learning. The mean value obtained by students’ during the Pre-Test only reached 61.00 and the mean value post-Test score for students’ after the treatment was 79.16. This shows that there was an increase in student learning outcomes. Based on the Paired Sample T-test where the sig (2-tailed) 0.000 was smaller than 0.05, meaning that Ha is accepted and H0 is rejected. It meant that there is a significant effect of video on SMAN 1 Inuman students’.